2006
DOI: 10.1093/nar/gkl1076
|View full text |Cite
|
Sign up to set email alerts
|

Cold shock domain proteins and glycine-rich RNA-binding proteins from Arabidopsis thaliana can promote the cold adaptation process in Escherichia coli

Abstract: Despite the fact that cold shock domain proteins (CSDPs) and glycine-rich RNA-binding proteins (GRPs) have been implicated to play a role during the cold adaptation process, their importance and function in eukaryotes, including plants, are largely unknown. To understand the functional role of plant CSDPs and GRPs in the cold response, two CSDPs (CSDP1 and CSDP2) and three GRPs (GRP2, GRP4 and GRP7) from Arabidopsis thaliana were investigated. Heterologous expression of CSDP1 or GRP7 complemented the cold sens… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
293
2

Year Published

2010
2010
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 243 publications
(310 citation statements)
references
References 37 publications
9
293
2
Order By: Relevance
“…2) (23). GR-RBPs have been shown to be involved in the plant's response to environmental stresses, particularly cold (45,46). However, little is known about the molecular function of either GR-RBPs or mRBPs.…”
Section: Discussionmentioning
confidence: 99%
“…2) (23). GR-RBPs have been shown to be involved in the plant's response to environmental stresses, particularly cold (45,46). However, little is known about the molecular function of either GR-RBPs or mRBPs.…”
Section: Discussionmentioning
confidence: 99%
“…WCSP1 complements the cold sensitive phenotype of the quadruple Csp-deletion strain of E. coli (BX04), indicating that this protein can function as an RNA chaperone in vivo in a bacterial system (30). Expression studies revealed that some Arabidopsis CSP transcripts are also increased upon cold stress treatment, indicating a potential role in cold adaptation (19,31,32). Arabidopsis thaliana cold shock domain proteins (AtCSPs) promote cold adaptation in bacteria (31)(32)(33)(34).…”
Section: Functions In Cold Stress Adaptationmentioning
confidence: 99%
“…Expression studies revealed that some Arabidopsis CSP transcripts are also increased upon cold stress treatment, indicating a potential role in cold adaptation (19,31,32). Arabidopsis thaliana cold shock domain proteins (AtCSPs) promote cold adaptation in bacteria (31)(32)(33)(34). Using functional approaches, AtCSPs were shown to play an important role under low temperature stress conditions in planta (33,34).…”
Section: Functions In Cold Stress Adaptationmentioning
confidence: 99%
See 2 more Smart Citations